2014
DOI: 10.4049/jimmunol.1303175
|View full text |Cite
|
Sign up to set email alerts
|

The Absence or Overexpression of IL-15 Drastically Alters Breast Cancer Metastasis via Effects on NK Cells, CD4 T Cells, and Macrophages

Abstract: IL-15 is a cytokine that can affect many immune cells, including NK cells and CD8 T cells. In several tumor models, IL-15 delays primary tumor formation and can prevent or reduce metastasis. In this study, we have employed a model of breast cancer metastasis to examine the mechanism by which IL-15 affects metastasis. When breast tumor cells were injected i.v. into IL-15 2/2 , C57BL/6, IL-15 transgenic (TG) and IL-15/IL-15Ra-treated C57BL/6 mice, there were high levels of metastasis in IL-15 2/2 mice and virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 52 publications
2
29
0
1
Order By: Relevance
“…In tumor transplantation model Gillgrass and colleagues recently demonstrated that Il15 ¡/¡ CD4 C T cells display a Th2 phenotype, which may be capable of polarizing macrophages to a pro-metastatic M2 phenotype while lung macrophages of Il15tg mice produce high levels of nitric oxide and IL-12, indicative of an anti-metastatic M1 polarized phenotype. 43,44 The increased tumorgenesis in Il15 ¡/¡ mice was found to be accompanied by increased levels of specific cytokines in serum, among them, IL-17, IFNg and IL-10. TH17 cytokines are expressed by TH17 cells and by innate lymphoid cells (ILCs) in response to IL-23 in the inflamed colon, 45 furthermore IL-17 has been described to promote angiogenesis and tumor growth 46 while IL-22 plays a dual protective and pro-inflammatory role in intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor transplantation model Gillgrass and colleagues recently demonstrated that Il15 ¡/¡ CD4 C T cells display a Th2 phenotype, which may be capable of polarizing macrophages to a pro-metastatic M2 phenotype while lung macrophages of Il15tg mice produce high levels of nitric oxide and IL-12, indicative of an anti-metastatic M1 polarized phenotype. 43,44 The increased tumorgenesis in Il15 ¡/¡ mice was found to be accompanied by increased levels of specific cytokines in serum, among them, IL-17, IFNg and IL-10. TH17 cytokines are expressed by TH17 cells and by innate lymphoid cells (ILCs) in response to IL-23 in the inflamed colon, 45 furthermore IL-17 has been described to promote angiogenesis and tumor growth 46 while IL-22 plays a dual protective and pro-inflammatory role in intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…administration of F-PLP/pIL15 generated higher IL15 expression levels in both ascites and the serum. This increased localized expression of IL-15 in the tumor microenvironment (ascites) could enhance antitumoral T-cell responses, while the increased serum levels may aid in the prevention of metastasis, thus jointly inhibiting tumor growth [28]. …”
Section: Resultsmentioning
confidence: 99%
“…First, the local instillation of T cell-recruiting factors (such as recombinant IFN-α2β or CXCL10) might be useful for the treatment of tumors that are defective in type I IFN signaling pathways 15 . Second, defects in MHC class I expression might be reverted (for instance, by the systemic administration of recombinant IFN-α2β or by the local provision of TLR agonists) or functionally bypassed (for instance, by using bispecific antibodies to target T cells to BCAAs or by using IL-15 to boost the cytotoxicity of NK cells, which are considered to be the main gatekeepers of MHC class I-deficient tumors) 132 . Third, exome sequencing may be used to detect mutations yielding potentially immunogenic BCAAs, which would open up the possibility of creating highly personalized peptide-based vaccines 133 .…”
Section: Discussionmentioning
confidence: 99%